ANTICOAGULANT AND ANTIOXIDANT ACTIVITIES OF THYMUS VULGARIS IN DEXAMETHASONE TREATED FEMALE ADULT RAT (Academicia Globe: Inderscience Research, 2023)
This experiment aimed to investigate the anticoagulant and anti-oxidant activities of Thymus vulgaris (T.vulgaris) in hyper coagulation induced by long time Dexamethasone administration. Twenty four adult female rats divided into 4 groups; 1st Control group, 2nd and 3rd groups had subcutaneous injection with Dex 0.1mg/kg 3 times/week for 60 days, then 3rd and 4th groups received 75 mg/kg of T.vulgaris orally for two weeks. At the end of the experiment blood samples were collected via heart puncture from anesthetized rats. Results revealed that dexamethasone for 74 days caused significant (p